Effects of PPM1K rs1440581 and rs7678928 on serum branched-chain amino acid levels and risk of cardiovascular disease. (1st January 2021) - Hu, Wen; Liu, Ziyu; Yu, Weinan; Wen, Surong; Wang, Xiaoqing; Qi, Xing; Hao, Hairong; Lu, Yanwen; Li, Jing; Li, Shayan; Zhou, Hongwen
Abstract: Objective: This study aimed to investigate the effects of PPM1K rs1440581 and rs7678928 single nucleotide polymorphisms (SNPs) on the serum branched-chain amino acids (BCAAs) levels and cardiovascular disease (CVD) risk. Methods: Anthropometric and biochemical examinations were performed at baseline and the end of 4 years in 234 individuals who were randomly recruited from the Diabetes Prevention Programme in Huai'an and received lifestyle intervention and follow up for 4 years. Serum BCAAs (leucine, isoleucine and valine (Val)) levels were measured by hydrophilic interaction chromatography-tandem mass spectrometric method and the PPM1K rs1440581 and rs7678928 were detected by high-throughput SNP genotyping at baseline. The associations of rs1440581 and rs7678928 with serum BCAA levels and risk for CVD after 4 years were further evaluated. Results: The distribution frequencies of PPM1K rs1440581 and rs7678928 met the Hardy-Weinberg equilibrium ( p> .05). The baseline serum levels of Val ( p = .022) and total BCAAs ( p = .026) in subjects with rs1440581 CC genotype were higher than in those with TT genotype. There were no significant differences in the serum levels of BCAAs among subjects with different genotypes of rs7678928. After 4-year follow-up, the subjects with rs1440581 CC genotype had higher systolic blood pressure (SBP) ( p = .027), diastolic blood pressure (DBP) ( p = .019), triglycerides (TGs) ( p = .019) and lower high-density lipoprotein cholesterol (HDL-c) ( p = .008) than those with TT genotype, and had higher AST level than those with TT ( p = .030) or TC ( p = .003) genotype; the subjects with rs7678928 TT genotype had higher SBP ( p = .039) and DBP ( p = .019) and lower HDL-c than those with CC ( p = .017) genotype. Lifestyle intervention had little influence on the serum levels of fasting plasma glucose (FPG), TG, HDL-c, alanine aminotransferase (ALT), AST and creatinine (CREA) in subjects with rs1440581 CC genotype or rs7678928 TT genotype ( p > .05). The incidences of CVD and non-alcoholic fatty liver disease (NAFLD) in subjects with rs1440581 CC genotype were higher than in those with TT genotype; the incidence of CVD in subjects with rs7678928 TT genotype was higher than in those with CC ( p < .05) genotype. Conclusions: Allele C of PPM1K rs1440581 was associated with elevated serum Val, total BCAAs and CVD risks. rs1440581 CC genotype may be a better marker than baseline serum BCAAs in predicting the risk for CVD. Trial registration: Diabetes Prevention Programme in Huai'an of Huai'an Second People's Hospital, ChiCTR-TRC-14005029. KEY MESSAGE: Allele C of PPM1K rs1440581 was relevant to elevated serum Val and total BCAAs. PPM1K rs1440581 CC and rs7678928 TT genotypes were associated with CVD risk. PPM1K rs1440581 CC genotype carriers were more likely to have liver injury and develop NAFLD.